Adjacency and vessel domestication as enablers of fish crimes - Belhabib, Dyhia; Le Billon, Philippe (Frontiers in Marine Science, 2022)
Fishery-related crimes, including illegal fishing, constitute major concerns including for coastal livelihoods and food security. This study examines the importance of adjacency, or legal presence within or in proximity to domestic fishing grounds and fish landing points, with regard to fishery crimes. Distinguishing between five main types of adjacency and examining cases from West Africa, the study finds that adjacency was a characteristic of a third of licensed vessels with reported fishery-related offenses in the region, 60% of which could be categorized as distant water fishing fleets. Fifty-four percent of the vessels authorized to fish in the region were foreign flagged, and 19% were foreign vessels reflagged to the coastal states, bringing up the contribution of foreign vessels to 73% of the fleets authorized to fish in the region. Vessel operators using a legal cover to commit infractions were mostly linked to China and Spain. This study points to the high likelihood of offense occurrence associated with the reflagging or “domestication” of foreign vessels, at least in West Africa, and the need to secure greater transparency and accountability in relation to access, offenses, and ownership.